A165 GENETIC DELETION OF HDAC1 AND HDAC2 DISRUPTS MURINE ENTEROID DEVELOPMENT AND METABOLIC PROGRAM. (1st March 2018) - Gonneaud, A; Turgeon, N; Jones, C; Couture, C; Boisvert, F; Boudreau, F; Asselin, C
Abstract: Background: Histone deacetylases HDAC1 and HDAC2 are homologous enzymes removing acetyl groups from histones and non-histone proteins. This epigenetic mark regulates many biological processes including cell proliferation and differentiation. We have shown that HDAC1 and HDAC2 drive intestinal epithelial cell (IEC) development and that Hdac1 and Hdac2 deletion in murine IEC disrupts intestinal architecture and IEC differentiation, leading to chronic colonic inflammation. Aims: We hypothesize that HDAC1 and HDAC2 display similar as well as distinct functions in IEC and that IEC-specific HDAC activity alterations modify basal IEC behavior and the intrinsic IEC response to environmental inflammatory signals. Methods: Jejunal villin-Cre Hdac1 or Hdac2 enteroids were established and grown in medium with or without SILAC, for proteome quantification by mass spectrometry. The transcriptome was assessed by RNA-Seq. Pathways were identified by bioinformatics approaches (DAVID, IPA). Villin-Cre ER Hdac1 and Hdac2 enteroids were treated with hydroxytamoxifen to induce gene deletion. The phenotype of Villin-Cre ER Hdac1 and Hdac2 as well as Villin-Cre Hdac1 and Hdac2 enteroids was observed by microscopy. To evaluate inflammatory response, enteroids were treated with TNF-α for 16h. Expression of selected targets was assessed by qPCR and Western blot Results: Embryonic or inducible deletion of Hdac1 and Hdac2 led to reduced enteroid growth and increased degeneration. Proteomic analysis of Hdac1 or Hdac2 deleted enteroids revealed shared enrichment of ontology terms, including metabolic and lipid metabolic processes or cell-cell adhesion. Transcriptomic analysis uncovered inflammatory response, immune system, retinol metabolic and oxydo-reduction processes and development ontology terms as being shared between HDAC1 and HDAC2. Transcriptomic analysis also revealed distinct pathways, namely response to virus and response to IFNγ upon Hdac2 deletion, and cholesterol homeostasis, ion transport and negative regulation of cell migration, upon Hdac1 deletion, among others, while proteomic analysis exposed many metabolic processes and ATP-dependent chromatin remodeling as distinct enriched ontology terms for Hdac1 deleted enteroids, and cellular responses to many environmental signals for Hdac2 deleted enteroids. TNF-α treatment induced apoptosis, as determined by Caspase 3 cleavage, in both mutated enteroids, while decreased NF-kB p65 phosphorylation was observed in Hdac2 deleted enteroids. Conclusions: HDAC1 and HDAC2 are necessary for intrinsic IEC growth. HDAC1 and HDAC2 regulate similar as well as distinct gene and protein expression programs, thereby indicating specific molecular functions in IEC. Selective inhibition of HDAC1 or HDAC2 in IEC by pharmacological agents could affect the mucosal response to inflammation. Funding Agencies: CCC, CIHR